2016
DOI: 10.1371/journal.pone.0148504
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Attention Gates Discrete Conscious Access to Past Sensory Stimuli

Abstract: Cueing attention after the disappearance of visual stimuli biases which items will be remembered best. This observation has historically been attributed to the influence of attention on memory as opposed to subjective visual experience. We recently challenged this view by showing that cueing attention after the stimulus can improve the perception of a single Gabor patch at threshold levels of contrast. Here, we test whether this retro-perception actually increases the frequency of consciously perceiving the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 37 publications
4
54
0
4
Order By: Relevance
“…Norman et al 2014;Faivre et al 2014; see also Ansorge et al 2014 for a review). On the other hand, several studies have shown that percepts which were not consciously registered by the subjects can later be brought into consciousness by attentional cues directed at the location of the stimulus after its disappearance (Kentridge 2013;Sergent et al 2013;Thibault et al 2016). This is important, as it lends support to the PEM idea that, by modulating the probability of the bottom-up signals, attention determines how much influence their probability should have on the posterior.…”
Section: The Problem Of Unconscious Perceptionmentioning
confidence: 93%
“…Norman et al 2014;Faivre et al 2014; see also Ansorge et al 2014 for a review). On the other hand, several studies have shown that percepts which were not consciously registered by the subjects can later be brought into consciousness by attentional cues directed at the location of the stimulus after its disappearance (Kentridge 2013;Sergent et al 2013;Thibault et al 2016). This is important, as it lends support to the PEM idea that, by modulating the probability of the bottom-up signals, attention determines how much influence their probability should have on the posterior.…”
Section: The Problem Of Unconscious Perceptionmentioning
confidence: 93%
“…In a series of experiments, my colleagues and I tested whether conscious perception could be triggered by retrospective attention [27,28]. Participants had to detect faint grids of oriented lines (Gabor patches) presented to the left or to the right of fixation, in one of two circles (figure 2a).…”
Section: Retro-perception: Perceiving the Pastmentioning
confidence: 99%
“…The interpretation of these parameters as products of separable psychological processes determining the quality and quantity of representation has led researchers to make claims of "discreteness" not only for working memory (W. Zhang & Luck, 2008) but also iconic (sensory) memory (Pratte, 2018) and even conscious visual perception (Thibault, van den Berg, Cavanagh, & Sergent, 2016;Asplund et al, 2014).…”
Section: Discussionmentioning
confidence: 99%